Antiviral regulation in porcine monocytic cells at different activation states - Sang, Yongming; Rowland, Raymond R.R.; Blecha, Frank (My University, 2014)
Monocytic cells, including macrophages and dendritic cells, exist in different activation states that are critical to the regulation of antimicrobial immunity. Many pandemic viruses are monocytotropic, including porcine reproductive and respiratory syndrome virus (PRRSV), which directly infects subsets of monocytic cells and interferes with antiviral responses. To study antiviral responses in PRRSV-infected monocytic cells, we characterized inflammatory cytokine responses and genome-wide profiled signature genes to investigate response pathways in uninfected and PRRSV-infected monocytic cells at different activation states. Our findings showed suppressed interferon (IFN) production in macrophages in non-antiviral states and an arrest of lipid metabolic pathways in macrophages at antiviral states. Importantly, porcine monocytic cells at different activation states were susceptible to PRRSV and responded differently to viral infection. Based on Gene Ontology (GO) analysis, two approaches were used to potentiate antiviral activity: (i) pharmaceutical modulation of cellular lipid metabolism and (ii) in situ PRRSV replication-competent expression of interferon alpha (IFN-α). Both approaches significantly suppressed exogenous viral infection in monocytic cells. In particular, the engineered IFN-expressing PRRSV strain eliminated exogenous virus infection and sustained cell viability at 4 days postinfection in macrophages. These findings suggest an intricate interaction of viral infection with the activation status of porcine monocytic cells. An understanding and integration of antiviral infection with activation status of monocytic cells may provide a means of potentiating antiviral immunity.
Keywords: Antiviral; Activation statuses; Macrophages; RNA-Seq; Porcine reproductive and respiratory syndrome virus